PENGARUH MODEL PEMBELAJARAN GI-GI (GROUP INVESTIGATION- GUIDED INQUIRY) PADA MATERI SISTEM EKSKRESI MANUSIA TERHADAP HASIL BELAJAR DI SMP 2 DRINGU KABUPATEN PROBOLINGGO - Grafika Ramadhanti Ekananda (ScienceEdu, 2023)
The low quality of science learning so far has been teacher-centered learning as a result of making students' scientific reasoning skills low because students are less given time to get science concepts. The purpose of this study was to determine the effect of the GI-GI learning model on student learning outcomes at SMP 2 DRINGU PROBOLINGGO REGENCY. The method used in this study is the GI-GI learning model by applying a type of quantitative research using quasi-experimental. Data collection techniques use observation. The research design used posttest only control group design using two classes, namely, one experimental class and one control class. This study was conducted to study the effect of the GI-GI (Group Investigation-Guided Inquiry) model on student learning outcomes on human excretory system material in junior high school. The data analysis techniques used are normality test, homogeneity test, and independent sample t-test. The results showed that the experimental group had an average of very good and good categories, while the control group had a good, medium and bad average which is a means that can be used to convey information to students, one of which is learning.